Investigation of microfilaria in sheep by using conventional techniques in Mosul City - Haneen Alabadi; sura Aghwan (Basrah Journal of Veterinary Research)
This study performed on 300 sheep in Mosul city from August 2024 to October 2024 for demonstration Microfilariae in sheep blood by use various methods such as Knott's technique, MG stain Giemsa, and fluorescent acridine orange staining. When detecting of microfilaria in the blood . The percentage of microfilaria infection is 56% during investigation by modified Knott technique. There were three forms of infection , mild ,moderate and severe infection with microfilariae in sheep using the same method showed significant differences in infection severity, below the limit of level (P < 0.05) .Also we studied the of risk factors such as age on the intensity of infection.,there was significant differences, a high percentage of infection was noticed in animals over three years old (93.1%) while low rat in sheep below one years old (27.1%). No significant differences noticed between the females (58%) and males (54%). The animals husbandry indicated increase level of infection out door system (61.6%) than indoor system (45.7%). Also there was significant differences between breed of the animals ,the infection rates in higher in export sheep (90%) than local breed (49.5%).